2020
DOI: 10.3390/su12219182
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Information Flow in Polish Construction Projects

Abstract: The objective of this paper is to analyse communication and information flow within construction projects on the basis of a survey study and a review of the literature. The subject of communication and its impact on carrying out a construction project is widely discussed in global academic literature. Many scholars point to problems with communication and information flow while also reporting that it directly affects construction project time and cost. In the literature, communication is also presented as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 84 publications
4
18
0
Order By: Relevance
“…In addition, appropriate information and communication channels must be ensured. The essence and importance of this investment project area is very strongly accentuated in the work of Kania et al [67], who indicate that a well-designed communication and information sharing system must encompass general information about communication and information flow between construction project participants, problems in carrying out construction projects in relation to the lack of effective communication, the impact of communication on the success of carrying out the construction project, communication costs, and the need to develop a tool (a digital system) that would support construction project managers in the optimal control over communication between project participants. It is important to keep in mind that the environment in which modern construction companies operate is becoming ever more informative [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, appropriate information and communication channels must be ensured. The essence and importance of this investment project area is very strongly accentuated in the work of Kania et al [67], who indicate that a well-designed communication and information sharing system must encompass general information about communication and information flow between construction project participants, problems in carrying out construction projects in relation to the lack of effective communication, the impact of communication on the success of carrying out the construction project, communication costs, and the need to develop a tool (a digital system) that would support construction project managers in the optimal control over communication between project participants. It is important to keep in mind that the environment in which modern construction companies operate is becoming ever more informative [5].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough analysis of communication and information flow within construction projects realized in Poland can be found in the study by Kania et al [67]. In a nutshell, communication and information channels, have a direct impact on the time and cost of a construction project.…”
mentioning
confidence: 99%
“…It has been emphasized by researchers (Stojcetovic et al , 2014) that top quality demands higher cost and time, but the practice of reducing the cost and time essential for the implementation of the project affects quality. Unfortunately, the observed quality issues are unrealized although many researchers have stressed upon the importance of the design process and early participation of construction experts in construction projects (Kania et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This paper highlighted 13 articles that show accuracies as one of the communication problems in various construction projects. These articles were written by (Kania et al, 2020;Khoury, 2019;Pandit et al, 2019;Ballesteros-Sánchez et al, 2019;Castillo et al, 2018;Kwofie et al, 2019;Eze et al, 2018;Tran et al, 2017;Yap et al, 2017;Al Mousli and El-Sayegh, 2016;Senaratne and Ruwanpura, 2016;Zulch, 2016;Chalker and Loosemore, 2016).…”
Section: Accuraciesmentioning
confidence: 99%
“…Time is considered one of these communication barriers as it is the barrier to creating quicker and faster communication channels. Several articles found that timeliness contributes to significant communication problems in construction projects (Kania et al, 2020;Akunyumu et al, 2019;Kwofie et al, 2019;Eze et al, 2018;Tran et al, 2017;Yap et al, 2017;Al Mousli & El-Sayegh, 2016;Senaratne & Ruwanpura, 2016;Chalker & Loosemore, 2016;Badi & Diamantidou, 2017).…”
Section: Timelinessmentioning
confidence: 99%